Occupational accidents in a woodcraft village in Vietnam - Vu Van, Thu; Truong Thi, Ly (International Journal of Occupational Safety and Health, 2025)
Introduction: In Vietnam, carpentry is one of fourteen main craft groups, making a significant contribution to socio-economic development. Carpentry villages are facing a fairly common situation of labor accidents. Meanwhile, research on occupational accidents in wood craft villages in Vietnam is still limited. This study focuses on studying the current situation of injuries caused by occupational accidents to workers in wood craft villages. Potential causes of injuries caused by occupational accidents are also researched, analyzed and clarified. Methods: The article is based on the qualitative research results of 05 in-depth interviews and the quantitative research results of 385 questionnaires. The research subjects are workers directly involved in wooden furniture production in La Xuyen wood craft villages. Results: The study shows that the situation of occupational accidents among direct workers in wood craft villages is very alarming and quite common, including serious and fatal occupational accidents. Occupational accidents happen to both men and women, in which men often suffer more serious and fatal occupational accidents than women. The main cause of occupational accidents is that production activities are spontaneous in nature, without safe working procedures. There are no labor safety regulations as well as labor safety instructions at the workplace. Conclusion: The study's findings promote the development of qualitative and quantitative research on issues related to occupational accidents and measures to prevent occupational accidents in wood craft villages. Vietnamese local authorities need to further strengthen their attention on ensuring occupational safety and health in the area, and promote propaganda and education to raise people's awareness in the prevention and control of occupational diseases or accidents. They also need to open training courses on instructions to operate machines and use personal protective equipment safely, and reduce the risks of occupational accidents for workers in the craft villages.